Pengembangan Buku Saku (E-Media) Termodinamika Berorientasi Android - Andi Putra Sairi (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2018)
Completing the teaching material is a task that must be carried out by the lecturer when carrying out pedagogical and pedagogical activities. A good learning tool is an element that must exist and must always be developed in order to improve the quality of learning in universities, such as learning materials. Indeed, the learning medium itself is a tool used to transmit knowledge to students in order to overcome the limitations of the senses, time and space. In addition, the availability of learning materials should also follow the evolution of the science and technology that is developing at this time. On this basis, efforts should be made to develop an educational resource in the form of an effective